Parasites infestation on juvenile tiger grouper (Epinephelus fuscoguttatus) nursed in net cage at Sea Farming Instalation Kepulauan Seribu, Jakarta - Yani Hadiroseyani; Irzal Effendi; Agnis Murti Rahayu; Heni Sela Arianty (Jurnal Akuakultur Indonesia)
This study was aimed to identify fauna parasite of juvenile tiger grouper (Epinephelus fuscoguttatus) on the two locations of floating net at Floating Net Sea Farming Center, Pulau Seribu Jakarta. A total of five tiger grouper fry from each location, checked every two weeks during the nursery period in August-September 2008 and June-August 2009. Parasites of young tiger grouper found were protozoa (Trichodina and myxosporea), monogenea Diplectanum, metaserkaria digenea, and isopods Alitropus. Diplectanum infestation was dominant with prevalence reached 100% and the average intensity of 2,87-72,8. Fish nursed in the Perairan Pulau Semak Daun was more susceptible compared to the fish nursed in Pulau Karang Congkak.